Analisis Pengelolaan Obat Di Puskesmas Cibalong Kecamatan Cibalong Tahun 2022 Berdasarkan Permenkes Ri Nomor 74 Tahun 2016 - Rizky Subagya; Kamiel Roesman Bachtiar; Ayu Rahmawati (Pusat Riset dan Inovasi Nasional, 2023)
Drug management at the puskesmas is an activity that includes planning needs, requests, receipts, storage, distribution, control, recording, reporting, archiving as well as management monitoring and evaluation. Drug management that is not ideal can be caused by drug planning that is only based on previous year's estimates, as well as inadequate facilities for the process of storing and distributing drugs. One way to overcome drug management that is not ideal is to compare the management of drugs at the health center with Permenkes number 74 of 2016 concerning pharmaceutical service standards at the health center. This study aims to find out how comfortable drug management is at the Cibalong Health Center with Permenkes Number 74 of 2016. This research was conducted using a qualitative method with a descriptive approach using interview guidelines and checklists based on Permenkes number 74 of 2016. Drug management data at Cibalong Health Center were taken from 3 sources, namely pharmacists, heads of health centers and pharmaceutical technical staff. From the results of the study, the results of interviews and checklists were obtained with the percentage value of planning (60%), request (83.33%), acceptance (60%), storage (72.22%), distribution (58.33%), control (60%), recording, reporting and filing (62.50%), management monitoring and evaluation (100%) with an overall average value of 69% with good criteria.